Pengaruh Fitur Muslim Friendly terhadap Perilaku Pelanggan Airbnb - Sahputra, Roza; Indra, Indra; Hussin, Mohd Fauzi bin Abu; Afifah, Kuni (Penerbit Goodwood, 2024)
Purpose: This research aims to analyze the influence of halal attributes, such as halal social environment, halal facilities, halal food and beverages, and services and staff of hotels or guesthouses, which are grouped into one variable, namely cognitive assessment, on consumer intention to visit, consumer willingness to pay, and WOM through Affective Assessment. Methods: This was a quantitative descriptive study. The data were processed using the Structural Equation Modeling (SEM) method through the partial least squares (PLS) or SEM-PLS approach. The data for this study were divided into two types: primary data obtained from questionnaires distributed online to 150 respondents in the Jakarta, Medan, and Kuala Lumpur areas. The testing consisted of two tests, namely the measurement test of the model (outer model) and the structural model test (inner model) using the SmartPLS3 tool. Results: Cognitive Assessment influences Intention to Visit, WOM, and Consumer Willingness to Pay through Affective Assessment by 90.6%, while the remaining 9.4% is explained by other constituent variables that are not explained in this study. Contribution: Adds variety to research on digital platforms and the diversity of culture, religion, and beliefs in the context of technology use. Limitations: At times, this research may face data limitations, especially if the data available from Airbnb or respondents are not sufficiently representative or complete.